Evaluasi Kinerja Operasional Terminal Cicaheum Bandung, Jawa Barat - Syukri, Muhammad; Garnida, Hendra (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The terminal is a movement node that provides a role as a stopover and a place for changing modes of transportation. The purpose of the research is to find out when the terminal is no longer able to accommodate buses parked in the courtyard or its capacity exceeds the maximum standard and to analyze the capacity of the Cicaheum Bus Terminal. The results of this study are based on a comparison of the area of the passenger terminal between the Minister of Transportation Regulation no. 132 of 2015 with the need for terminal area in Bandung Cicaheum Terminal with a total area of 11,935 m2, where the total figure is still lacking or not in accordance with the standards set by PERMENHUB NO. 132 of 2015, namely 23,494 m2. , And from the results of the capacity analysis, how long can the terminal parking lot accommodate AKDP AKAP buses, namely 105 years with an assumption of 2% growth in the number of vehicles, if where the greater the % growth in the number of vehicles, the faster the terminal capacity will be maximum